2022
DOI: 10.3390/cancers14112679
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profile and Diagnostic Significance of MicroRNAs in Papillary Thyroid Cancer

Abstract: The incidence of papillary thyroid cancer (PTC) has increased in recent years. To improve the diagnostic management of PTC, we propose the use of microRNAs (miRNAs) as a biomarker. Our aim in this study was to evaluate the miRNA expression pattern in PTC using NanoString technology. We identified ten miRNAs deregulated in PTC compared with reference tissue: miR-146b-5p, miR-221-3p, miR-221-5p, miR-34-5p, miR-551b-3p, miR-152-3p, miR-15a-5p, miR-31-5p, and miR-7-5p (FDR < 0.05; |fold change (FC)| ≥ 1.5). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 90 publications
0
25
0
Order By: Relevance
“…Papillary thyroid cancer can be diagnosed with an ultrasound, FNA, and cytology testing. However, it is sometimes impossible to differentiate between malignant and benign tissue at a preoperative stage ( 4 ). Some investigations have revealed that the expression of specific miRNAs can be associated with characteristics such as tumor size, capsular and vascular invasion, and tumor aggressiveness ( 47 ).…”
Section: Analysis Of Micrornas In Tumoral Tissue Of Ptcmentioning
confidence: 99%
See 3 more Smart Citations
“…Papillary thyroid cancer can be diagnosed with an ultrasound, FNA, and cytology testing. However, it is sometimes impossible to differentiate between malignant and benign tissue at a preoperative stage ( 4 ). Some investigations have revealed that the expression of specific miRNAs can be associated with characteristics such as tumor size, capsular and vascular invasion, and tumor aggressiveness ( 47 ).…”
Section: Analysis Of Micrornas In Tumoral Tissue Of Ptcmentioning
confidence: 99%
“…Rogucki and colleagues have shown that a panel of four miRNAs (miR-152-3p, miR-221-3p, miR-551b-3p, and miR-7-5p) could be used for the diagnosis of PTC. Furthermore, miR-152-3p, miR-221-3p, and miR-7-5p target EGFR gene regulation ( 4 ). The EGFR gene is a tyrosine kinase involved in cell proliferation, and mutations in this gene are associated with PTC tumor cell development ( 48 ).…”
Section: Analysis Of Micrornas In Tumoral Tissue Of Ptcmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, it is known that RAS mutations influence miRNA expression profiles in thyroid tumors [22,23]. However, authors mostly focused on differential miRNA expression between malignant and benign tumors, without considering the presence of RAS mutations as a confounding factor [24][25][26]; on the contrary, several miRNAs are known to be specifically deregulated in BRAF mutant thyroid tumors compared to wild-type cases [27,28]. In previous studies from our group, we demonstrated that wild-type NIFTPs show a benign-like miRNA phenotype, while RAS-mutant NIFTPs show a malignant-like miRNA phenotype [29,30]; in detail, 12 miRNAs were significantly deregulated in mutant versus wild-type NIFTPs (miR-221-5p, miR-221-3p, miR-222-3p, miR-146b-5p, miR-181a-3p, miR-28-5p, miR-363-3p, miR-342-3p, miR-1285-5p, miR-152-3p, miR-25-3p, miR-30e-3p) [30].…”
Section: Discussionmentioning
confidence: 99%